Aplikasi Sistem Pakar Berbasis Android dengan Metode Certainty Factor untuk Mendiagnosis Penyakit pada Tanaman Karet - Bambang Hermanto; Albertus Sudirman; Akmal Junaidi; Arif Pebriansyah (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Rubber is an important plantation commodity as a source of income, employment and foreign exchange opportunities, as an engine of economic development in new centers within the rubber plantation environment. Rubber plant diseases generally cause economic losses to rubber plantations. Lack of knowledge of farmers to control rubber plant diseases can result in losses and ultimately reduce farmers' income. Therefore, it is necessary to build a system that can diagnose diseases like an expert or an expert. The method used in this system is the certainty factor method which is used to prove whether a fact is certain or uncertain. This method is very suitable for expert systems that diagnose uncertainty. After that, a system validity test is carried out which aims to test the ability of the expert system to identify diseases. Based on the test results, the highest disease score was tapping groove disease with a disease percentage of 94.96%, while the lowest disease percentage was red root fungus disease with a percentage of 79%, with an average test result above 75% so that it was concluded that the system can diagnose rubber plant diseases well in accordance with the results of the diagnosis obtained.